Forage, preen or fight? A study of interspecific water bird interactions at Crișul Repede River - Ana-Teodora ȘTEFAN; Cristina CRAIOVEANU; Alexandru Nicolae STERMIN (Studia Universitatis Babeș-Bolyai. Biologia)
Analyzing the behavior of birds offers insight into the conservation of biodiversity, a heavily discussed subject in the fields of ecology as well as ornithology. As it has been previously proven (Rushton et al., 1994), slow-flowing areas of rivers represent important habitats for birds all throughout the year and the conservation of this type of habitats has been known to have a positive effect on the population of many water bird species (Rolls et al., 2012). Therefore, this study explores the dynamic of interspecific interactions between water birds in open water areas from the Afon Peța portion of the Crișul Repede River in Bihor, Romania. We collected data over 8 months, from October 2022 to May 2023 and identified 23 bird species and three types of interactions between them: cooperation for foraging, for grooming, and aggression. The frequency of various interactions was directly proportional to the number of individuals observed on the area, however, we found no connection to the month or the season. Additionally, we detected no preference regarding the interaction partner species. We found a strong correlation between the number of individuals and the number of interactions in all species. The results obtained through this study will help broaden the knowledge about common aquatic bird species in the area, as well as the dynamic of behaviours over the course of three seasons.